Pengaruh Penambahan Zat Aditif Graphene Terhadap Karakteristik Lapis Tipis Aspal Pasir (Latasir) A - Putra, Rahmat Ade; Shalahuddin, Muhammad; Alwinda, Yosi; Amri, Amun (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Latasir or a thin layer of asphalt sand is a pavement surface covering consisting of fine aggregates or sand or a mixture of both hard and asphalt mixed, stretched and compacted under certain conditions. Itis often used on the streets as light as local roads or road environment, in order to restrain the rate of water so as not to enter into pores in it. One of the efforts made to improve the quality of asphalt pavementby modifying the mixture material with the addition of certain additives. Graphene is thought to be able to become another asphalt addictive. Several previous studies used Grpahene in various reinforcementstructures. The purpose of this study was to determine the value of Marshall characteristics in the mixtureof Latasir A using graphene addictive. Variation made in this study were 0% (without mixture), 2%, 2.5%, and 3% for the presentation value of asphalt density as a comparison of the value of stability, flow, VMA, VIM, VFA and MQ. The results of this study indicate that the addition of graphene as an addictive to the asphalt mixture tends to increase the value of stability, the value of melt (flow) so that it becomesmore elastic because it is above the specification limit, and not too much increase in the value of the VIM, VMA, VFA, and Marshall Quotient (MQ) value. For the best Marshall Characteristics, the addition ofgraphene is 3% and the optimum asphalt content (KAO) is 8,50% with a stability value of 580 kg, flow value of 4.10%, VIM 4.50%, VFA 79.00%, VMA 22.30% and MQ 140.00 Kg / mm.Keywords: graphene, additives, Latasir, Marshall Characteristics